Connecting - Helen Walker; JoAnne Katzmarek; Steven L. VanderStaay; Irwin Ramirez Leopando; Christopher Sweet; Howard Wolf (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
JoAnne Katzmarek—Thoughts Like Flying Grouse Steven L. VanderStaay—I'm With You, Huck Irwin Ramirez Leopando—A Moment of Connections Christopher Sweet—The Brightening Glance Howard Wolf—Personal Teaching